Important implementation constructs for federal agencies in health and human service settings that are selecting, monitoring, and supporting grantees. (1st August 2020) - Dymnicki, Allison; Bzura, Robin; Osher, David; Wandersman, Abraham; Duplantier, Dan; Boyd, Michelle; Cash, Amanda; Hutchison, Lindsey
Abstract : Background: Federal agencies and other funders seeking to maximise their impact aim to understand factors associated with implementing evidence-based interventions (EBIs) to address health problems. Challenges exist, however, in synthesising information from different disciplines and reaching agreement about these factors due to different terminology, frameworks, and measures being used in different fields. Methods: A mixed-methods approach was used to identifying a set of implementation constructs helpful for selecting, monitoring, and supporting federal grantees in health and human service settings. Three phases of research were conducted: a literature review, structured expert interviews, and consensus building. Interviews with implementation experts were used to validate a set of implementation constructs identified in the literature review as strongly and consistently related to successful implementation of EBIs in international contexts. A modified Delphi approach was used with a technical working group (TWG) of federal staff to agree on the constructs most relevant for federally funded EBIs. Findings: This process yielded 11 constructs related to either the intervention, the intersection between the invention and context, or the implementation process. These constructs are areas of interest when integrating research evidence into routine practice. Expert interviewees recommended establishing clear, consistent construct definitions before developing valid, feasible measures of the constructs. In contrast to the numerous and specific constructs advanced by researchers, federal TWG members favoured fewer constructs with more generalisability. Discussion and conclusions: This article demonstrates the translation work required for policy contexts and highlights a successful approach to translate evidence from implementation science research for federal staff.